Positive electrode material and preparation method thereof, battery and electric equipment
By uniformly doping Zr and Y/Al in the positive electrode material and forming a cladding layer, the problem of reducing electrical performance caused by uneven distribution of doped elements is solved, and the electrical performance of the positive electrode material is significantly improved.
Patent Information
- Application Number
- CN202411039220.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-04-04
AI Technical Summary
The metal elements doped in the existing positive electrode materials are unevenly distributed, resulting in a decrease in electrical performance.
A positive electrode material is used, which includes the matrix material LiNiaCobMncM1dM2fO2 and the cladding layer LigXBOh, M1 is Zr, M2 is at least one of Y and Al, and X is certain metal elements. The cladding layer is generated by reacting nano-XB with free lithium on the surface of the matrix material.
By uniform doping of M1 and M2, the problem of uneven distribution is avoided, and the electrical performance of the positive electrode material is significantly improved, including low temperature efficiency, specific capacity and cycling performance. The cladding layer increases the diffusion path of Li+, further improving electrical performance.
Smart Images

Figure CN119764361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a positive electrode material and a preparation method thereof, a battery and an electrical device. Background Art
[0002] In the related art, positive electrode materials, such as nickel-cobalt-manganese materials, are usually doped with cationic compound additives. However, the metal elements doped in the positive electrode materials are unevenly distributed, resulting in excessive content of local metal elements, which leads to reduced electrical properties of the positive electrode materials.
[0003] It is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention
[0004] An object of the present invention is to provide a new technical solution for positive electrode materials.
[0005] According to a first aspect of the present invention, a positive electrode material is provided. The positive electrode material comprises a base material and a coating layer coated on the surface of the base material, wherein the coating layer covers the surface of the base material, and the chemical formula of the base material is LiNi a Co b Mn c M1 d M2 f O2, the chemical formula of the coating layer is Li g XBO h , wherein a is 0.6 to 0.95, b is 0.02 to 0.20, c is 0.03 to 0.20, d is 0.002 to 0.02, f is 0.0004 to 0.01, g is 2.025 to 4, h is 4.0875 to 8, M1 is Zr, M2 is at least one of Y and Al, X is one of Ti, Zr, Al, Mg, Zn, V, Ru, Y, W, Na, K, Rb, Cs, Sc, Nb, Bi, Co, Ni, Mn, Mo, Ta, Sr, La, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence state is the same.
[0006] Optionally, the molar ratio of B to X is from 0.5 to 1.
[0007] Optionally, X and the LiNi a Co b Mn c M1 d M2 f The mass ratio of O2 is 400ppm to 4000ppm.
[0008] Optionally, M1 and the LiNi a Co b Mn c M1 d M2 f The molar ratio of O2 is 0.002 to 0.02.
[0009] Optionally, the molar ratio of M1 to M2 is 9 / 2 to 2 / 1.
[0010] According to the second aspect of the present application, a method for preparing the positive electrode material as described above is provided. The method comprises:
[0011] The precursor Ni a Co b Mn c (OH)2, lithium source, M1M2Ox are mixed and sintered to obtain the matrix material, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence state is the same;
[0012] The LiNi a Co b Mn c M1 d M2 f O2 and a coating agent are mixed to react and generate the positive electrode material, the coating agent forms the coating layer, and the coating agent includes nano-XB.
[0013] Optionally, the LiNi a Co b Mn c M1 d M2 f The surface of O2 has free lithium, and the concentration of the free lithium is 300ppm-1300ppm.
[0014] Optionally, the free lithium includes at least one of LiOH or Li2CO3.
[0015] Optionally, in LiNi a Co b Mn c M1 d M2 f In O2, the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is 0.8 to 1.6.
[0016] Alternatively, LiNi a Co b Mn c M1 d M2f The specific surface area of O2 is 0.6 g / cm 3 Up to 1.4g / cm 3 .
[0017] Optionally, during the sintering, the mixed materials are first sintered at 500° C. to 800° C. for 1 to 3 hours, and then the temperature is raised to 850° C. to 1100° C. and sintered for 8 to 20 hours.
[0018] Optionally, the LiNi a Co b Mn c M1 d M2 f O2 and the coating agent are mixed and reacted to generate the positive electrode material, the coating agent forms the coating layer, and the coating agent includes nano-XB. The steps include: reacting the mixed material at 120°C-200°C for 2 hours to 12 hours.
[0019] Optionally, in M1M2O x , x = 2.1 to 2.2.
[0020] Optionally, the precursor Ni a Co b Mn c The particle size D10, particle size D5 and D90 of (OH)2 satisfy: D50 is 2μm-4μm; (D90-D10) / D50=0.5-0.7.
[0021] Optionally, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium sulfate, lithium chloride, lithium acetate, lithium oxalate, and lithium nitrate.
[0022] Optionally, the lithium source and the precursor Ni a Co b Mn c The molar ratio of (OH)2 is 0.8 to 1.6.
[0023] Optionally, the particle size D50 of nano-XB is 1 μm to 5 μm; the specific surface area of nano-XB is greater than 5 m 2 / g.
[0024] According to a third aspect of the present application, a battery is provided, which includes the positive electrode material described in the present application.
[0025] According to a fourth aspect of the present application, an electrical device is provided, which includes the battery described in the present application.
[0026] In the positive electrode material provided in this application, Ni 2+ 、Ni 3+ 、Co3+ , Mn 4+ ions, and the M1 valence state is similar to that of Mn 4+ The valence state of M2 is consistent with that of Co 3+ 、Ni 3+ The valence state of the metal element X in the coating agent reacts with the free lithium on the surface of the single crystal material to form a coating layer, which increases the Li + The diffusion path of the positive electrode further improves the electrical performance of the positive electrode material.
[0027] In addition, since M1 and M2 of the present application are uniformly doped in the matrix material, M1 and M2 will not be locally gathered on the surface of the matrix material, which makes the surface of the matrix material covered with the coating layer as a whole.
[0028] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0030] Figure 1 This is an electron microscope image of the positive electrode material according to Example 1 of the present application.
[0031] Figure 2 This is an EDS bright field image of the positive electrode material according to Example 1 of the present application.
[0032] Figure 3 This is a surface distribution diagram of the oxygen element in the positive electrode material according to Example 1 of the present application.
[0033] Figure 4 This is a surface distribution diagram of the nickel element in the positive electrode material according to Example 1 of the present application.
[0034] Figure 5 This is a surface distribution diagram of the cobalt element in the positive electrode material according to Example 1 of the present application.
[0035] Figure 6 This is a surface distribution diagram of the manganese element in the positive electrode material according to Example 1 of the present application.
[0036] Figure 7 This is a surface distribution diagram of the zirconium element in the positive electrode material according to Example 1 of the present application.
[0037] Figure 8 This is a surface distribution diagram of the yttrium element in the positive electrode material according to Example 1 of the present application.
[0038] Fig. 9 This is a surface distribution diagram of the tungsten element in the positive electrode material according to Example 1 of the present application.
[0039] Fig.10 This is a surface distribution diagram of the boron element in the positive electrode material according to Example 1 of the present application.
[0040] Fig.11 This is a surface scan content diagram of different elements in the positive electrode material according to Example 1 of the present application. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0042] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0043] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.
[0044] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0045] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0046] According to one embodiment of the present application, a positive electrode material is provided. The positive electrode material comprises a base material and a coating layer coated on the surface of the base material, wherein the coating layer covers the surface of the base material, and the chemical formula of the base material is LiNi a Co b Mn c M1 d M2 f O2, the chemical formula of the coating layer is Li g XBO h, wherein a is 0.6 to 0.95, b is 0.02 to 0.20, c is 0.03 to 0.20, d is 0.002 to 0.02, f is 0.0004 to 0.01, g is 2.025 to 4, h is 4.0875 to 8, M1 is Zr, M2 is at least one of Y and Al, X is one of Ti, Zr, Al, Mg, Zn, V, Ru, Y, W, Na, K, Rb, Cs, Sc, Nb, Bi, Co, Ni, Mn, Mo, Ta, Sr, La, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence state is the same.
[0047] Specifically, the positive electrode material is used for the positive electrode of the battery. The base material of the positive electrode material is a single crystal material, namely LiNi a Co b Mn c M1 d M2 f O2. The surface of the single crystal material is coated with a coating layer, namely Li g XBO h. In the present application, nickel can increase the volume energy density of the positive electrode material, but too high a nickel content will lead to lithium-nickel mixing in the positive electrode material, causing lithium precipitation. a is 0.6 to 0.95. Within this range, both the volume energy density of the positive electrode material can be guaranteed to be high and lithium precipitation can be avoided. Optionally, the value of a can be but is not limited to 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc. Cobalt can stabilize the layered structure of the positive electrode material and can improve the cycle stability and rate performance of the positive electrode material, but too high a cobalt content can easily lead to a decrease in the capacity of the positive electrode material. b is 0.02 to 0.20. Within this range, both the layered structure of the positive electrode material can be guaranteed to be stable and the capacity of the positive electrode material can be large. Optionally, the value of b can be, but is not limited to, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, etc. Manganese can improve the safety of the positive electrode material, but too high a manganese content will destroy the layered structure of the positive electrode material. c is 0.03 to 0.20. Within this range, both the safety of the positive electrode material and the stability of the layered structure of the positive electrode material can be ensured. For example, the value of c can be but not limited to 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, etc. M1 and M2 can improve the ionic conductivity of the positive electrode material and reduce the degree of lithium ion mixing. However, too high a content of M1 and M2 will destroy the structural stability of the positive electrode material, destroy the electron transmission channel, and affect the charge and discharge performance. d is 0.002 to 0.02. f is 0.0004 to 0.01. Within this range, both the high ionic conductivity of the positive electrode material and the structural stability of the positive electrode material can be ensured. Optionally, the value of d may be, but is not limited to, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, etc. The value of f may be, but is not limited to, 0.0004, 0.00045, 0.0005, 0.0006, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, etc.
[0048] The free lithium on the surface of the single crystal material can react with the coating agent to form a coating layer, which can form a stable physical barrier, inhibit side reactions, improve charge transfer kinetics, and improve the material cycle stability. However, the surface pollutants with poor conductivity such as Li2CO3 and LiOH in the free lithium will hinder the transmission of ions and electrons, increase impedance, and thus lead to unsatisfactory reversible capacity, cycle performance, high temperature performance and safety performance of the battery. g is 2.025 to 2.5. Within this range, a stable coating layer can be formed on the surface of the base material, and pollutants on the surface of the positive electrode material can be reduced. Optionally, the value of g can be but not limited to 2.025, 2.03, 2.15, 2.18, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 3, 3.5, 4, etc. The oxygen in the coating layer matches the valence state of the metal cations in the coating layer. Optionally, the value of h can be but is not limited to 4.0875, 4.09, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.75, 6, 6.5, 7, 7.5, 8, etc.
[0049] In addition, within the above ranges of a, b, c, d, f, g and h, the valence state of M1 is similar to that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence states of M1 and M2 are the same, so that M1 and M2 can be evenly distributed in the positive electrode material.
[0050] In the embodiment of the present application, the base material is a single crystal material. The single crystal material also contains Ni 2+ 、Ni 3+ 、Co 3+ , Mn 4+ ions. And the M1 valence state is similar to that of Mn 4+ The valence state of M2 is consistent with that of Co 3+ 、Ni 3+ The valence state of the single crystal material is consistent, which significantly reduces the semiconductor effect of the matrix material, so that M1 and M2 are uniformly doped in the matrix material, avoiding the uneven distribution of doping elements and significantly improving the electrical properties of the positive electrode material. For example, the low-temperature efficiency, specific capacity and cycle performance of the positive electrode material are all high. The metal element X in the coating agent reacts with the free lithium on the surface of the single crystal material to form a coating layer, which increases the Li + The diffusion path of the positive electrode further improves the electrical performance of the positive electrode material.
[0051] In addition, since M1 and M2 of the present application are uniformly doped in the matrix material, M1 and M2 will not locally aggregate on the surface of the matrix material, and M1 and M2 will not damage the coating layer, which makes the coating layer on the surface of the matrix material uniformly distributed. + diffusion path.
[0052] In one example, the molar ratio of B to X is 0.5 to 1.
[0053] When the molar ratio of B to X is less than 0.5, the coating layer may have an incomplete structure or a small thickness, and may not effectively protect the base material. When the molar ratio of B to X is greater than 1, the coating layer may be too thick, thereby affecting the structural stability of the positive electrode material, and may cause the positive electrode material to expand in volume or undergo a structural phase change. In addition, the amount of X is too small to effectively react with the free lithium on the surface of the base material. Optionally, the molar ratio of B to X is 0.6, 0.7, 0.8, 0.9, etc.
[0054] Within this range, the coating layer has a uniform thickness and a complete structure, can be more evenly distributed on the surface of the base material, and the metal element X can fully react with the free lithium on the surface of the base material.
[0055] In one example, X and the LiNi a Co b Mn c M1 d M2 f The mass ratio of O2 is 400ppm-4000ppm. Within this range, the metal element X can fully react with the free lithium on the surface of the matrix material.
[0056] The X element can react with the free lithium on the surface of the matrix material to form a coating layer. a Co b Mn c M1 d M2 f When the mass ratio of O2 is less than 400ppm, X cannot react effectively with free lithium. a Co b Mn c M1 d M2 f When the mass ratio of O2 is greater than 4000ppm, the coating layer thickness is too large, thereby affecting the structural stability of the positive electrode material. a Co b Mn c M1 d M2 fThe mass ratio of O2 is 400ppm, 600ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, etc.
[0057] Within the above range, it is possible to ensure that the X element fully reacts with the free lithium on the surface of the matrix material, and the thickness of the coating layer is moderate, and the structural stability of the positive electrode material is high.
[0058] In one example, M1 and LiNi a Co b Mn c M1 d M2 f The molar ratio of O2 is 0.002 to 0.02.
[0059] Zr can improve the cycle stability of positive electrode materials. Zr and LiNiaCobMncM1 d M2 f When the molar ratio of O2 is less than 0.002, the cycle stability of the positive electrode material cannot be effectively improved. d M2 f When the molar ratio of O2 is greater than 0.02, the structural stability of the matrix material will be reduced and the diffusion of lithium ions will be hindered. a Co b Mn c M1 d M2 f The molar ratio of O2 is 0.02, 0.003, 0.004, 0.005, 0.006, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, etc.
[0060] Within this range, the cycle stability of the positive electrode material can be guaranteed and the structural stability of the material can be improved.
[0061] In one example, the molar ratio of M1 to M2 is 2 to 4.5.
[0062] When the molar ratio of M1 to M2 is greater than 4.5, the crystal structure of the positive electrode material changes, destroying the structural stability, thereby affecting the cycle life and safety of the battery. When the molar ratio of M1 to M2 is less than 2, the cycle stability and electrochemical performance of the positive electrode material are reduced. Optionally, the ratio of the two is 2.2, 2.5, 3.0, 3.5, 4.0, etc.
[0063] Within this range, the cycle stability of the positive electrode material can be guaranteed and the structural stability and electrochemical performance of the material can be improved.
[0064] According to another embodiment of the present application, a method for preparing the positive electrode material described in the present application is provided. The preparation method comprises:
[0065] S1, the precursor Ni a Co b Mn c (OH)2, lithium source, M1M2Ox are mixed and sintered to obtain the matrix material, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence states are the same, among which M1M2Ox is a composite oxide;
[0066] S2, LiNi a Co b Mn c M1 d M2 f O2 and a coating agent are mixed to react and generate a positive electrode material, the coating machine forms the coating layer, and the coating agent includes nano-XB.
[0067] Specifically, the precursor Ni a Co b Mn c (OH)2 is synthesized by batch method or continuous method. a Co b Mn c (OH)2 is a small particle size particle material. Small particle size particles can improve the precursor Ni a Co b Mn c Reactivity of (OH)2. Precursor Ni a Co b Mn c The primary crystals of (OH)2 are in the shape of laths, needles or blocks, wherein in the X-ray diffraction (XRD) test, FWHM(001)=0.2-0.6, FWHM(101)=0.2-0.8. For example, FWHM(001) is 0.2, 0.3, 0.4, 0.5, 0.6, etc. FWHM(101) is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc.
[0068] The lithium source may be, but is not limited to, at least one of lithium hydroxide, lithium carbonate, lithium sulfate, lithium chloride, lithium acetate, lithium oxalate, and lithium nitrate.
[0069] M1M2Ox is a composite oxide. Composite oxide refers to a compound composed of two or more metal elements and oxygen elements. Compared with a single metal oxide, a composite oxide has a variety of crystal structures, metal ions with a variety of valence states, and a higher chemical reactivity. In M1M2Ox, M1 is Zr and M2 is Y and / or Al. x = 2.1-2.2. If the x value is too large, that is, the oxygen content is too high, the crystal structure will change when the matrix material is generated by the reaction, affecting the structural stability of the matrix material. If the x value is too small, that is, the oxygen content is insufficient, the doping effect of Zr and M2 (Al and / or Y) will be weakened, affecting the electrochemical properties of the positive electrode material. Within this range, the crystal structure of the matrix material can be guaranteed to be stable, and the doping effect of Zr and M2 (Al and / or Y) can be guaranteed to be good. For example, x is 2.1, 2.11, 2.12, 2.14, 2.15, 2.16, 2.17, 2.18, 2.19, 2.2, etc.
[0070] X in the coating agent nano-XB is one of Ti, Zr, Al, Mg, Zn, V, Ru, Y, W, Na, K, Rb, Cs, Sc, Nb, Bi, Co, Ni, Mn, Mo, Ta, Sr, and La. The B element can improve the room temperature charging capacity of the positive electrode material, and the B element has a catalytic effect, which can make the X element react with free lithium at room temperature. For example, the particle size D50 of nano-XB is 1μm to 5μm. For example, the particle size D50 is 2μm, 3μm, 4μm, etc. The specific surface area of nano-XB BET>5m 2 / g. For example, the specific surface area is 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, etc.
[0071] If the particle size D50 of nano-XB is too small, it is easy to agglomerate. If the particle size D50 of nano-XB is too large, its chemical reaction activity is low and it is not easy to react with free lithium. Within this range, nano-XB can avoid agglomeration and fully react with free lithium. If the specific surface area of nano-XB is too small, the number of active sites exposed on its surface is small, making it difficult to react with free lithium at low temperatures, and the formation of the coating layer is incomplete. Within this specific surface area range, nano-XB can be guaranteed to react with free lithium at room temperature.
[0072] During the preparation, first, a base material is synthesized in step S1; then, the base material is coated in step S2.
[0073] In step S1, the precursor Ni a Co b Mn c (OH)2, lithium source, M1M2Ox, according to the molar ratio M(Li):M(precursor) = 0.8-1.6, M1 and Ni a Co b Mn c The molar ratio of (OH)2 is 0.002-0.02, and the molar ratio of M1 to M2 is 2 to 4.5, which are added to a high-speed mixer and stirred at a medium speed of 650rpm-1200rpm (optionally, the rotation speed is 650rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, etc.) for 4min-7min. Optionally, the stirring time is 4min, 5min, 6min, 7min, etc. Among them, a too low ratio of M(Li) to M(precursor) will result in incomplete reaction of the precursor, and a too high ratio will result in excessive free lithium in the matrix material. Optionally, the molar ratio is 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, etc. Within the above range, the lithium reacts fully with the precursor. M1 and Ni a Co b Mn c The molar ratio of (OH)2 is within the above range, so that the distribution of Zr element in the positive electrode material is uniform. Optionally, the molar ratio is 0.02, 0.003, 0.004, 0.005, 0.006, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, etc. M1 and Ni a Co b Mn c The molar ratio of (OH)2 is 0.002-0.02, so that M1 and (LiNi a Co b Mn c M1 d M2 f O2) in a molar ratio of 0.002 to 0.02.
[0074] Then, stir at a high speed of 1500rpm-2000rpm for 25min-35min, optionally, the stirring speed is 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm, 2000rpm, etc., and the stirring time is 25min, 26min, 27min, 28min, 29min, 30min, 31min, 32min, 33min, 34min, 35min, etc. Next, place the mixed material in a crucible, the filling amount is 2kg-8kg, optionally, the filling amount is 2kg, 3kg, 4kg, 5kg, 6kg, 7kg, 8kg, etc. The crucible is placed in a box furnace, and the material is sintered in an oxygen atmosphere (for example, an oxygen content of 99.5%-99.9%). For example, during the sintering process, the temperature in the furnace is raised to 500°C-800°C and kept for 1h-3h. Optionally, the temperature is 500°C, 600°C, 700°C, 800°C, etc., and the holding time is 1h, 1.5h, 2h, 2.5h, 3h, etc.; then, the temperature is raised to 850°C-1100°C and kept for 8-20h. Optionally, the temperature is 850°C, 900°C, 950°C, 1000°C, 1050, 1100°C, etc., and the holding time is 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc. The sintered material is crushed to prepare a powder. For example, the sintered material is airflow crushed in an airflow pulverizer. For example, the frequency of the separation motor of the air flow mill is 100Hz-200Hz, and optionally, the frequency is 100Hz, 110Hz, 120Hz, 130Hz, 140Hz, 150Hz, 160Hz, 170Hz, 180Hz, 190Hz, 200Hz, etc. The frequency of the feeding motor is 1Hz-5Hz, and optionally, the frequency is 1Hz, 2Hz, 3Hz, 4Hz, 5Hz, etc. The dust collection backflush / interval time is 10s / 0.5s, the air pressure is 0.2MPa-0.8MPa, optionally, the air pressure is 0.2MPa, 0.3Mpa, 0.4Mpa, 0.5Mpa, 0.6Mpa, 0.7MPa, 0.8MPa, etc., to obtain a matrix material with an average primary particle size of 0.5μm-5μm, optionally, the average primary particle size is 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc. The chemical formula of the matrix material is LiNi a Co b Mn c M1 d M2 f O2.
[0075] M1M2Ox is doped into the matrix material as a dopant. M1M2Ox is a composite oxide. The molecular structure of M1M2Ox includes M1 and M2 metal cations, not a mixture of multiple oxides. Since the molecular structure of M1M2Ox includes M1 and M2 metal cations, when doping, M1 and M2 can be doped together in the nickel-cobalt-manganese ternary material. Since Ni 2+ 、Ni 3+ 、Co 3+ , Mn 4+ Ion. M1 valence state and Mn 4+ The valence state of M2 is consistent with that of Co 3+ 、Ni 3+ The valence state of the metal is consistent, which significantly reduces the semiconductor effect of the matrix material, so that M1 and M2 are uniformly doped in the matrix material, avoiding uneven distribution of doping elements and significantly improving the electrical properties of the positive electrode material. However, the oxide of a single metal, such as ZrO2, Y2O3, and Al2O3, has only one cation in its molecular structure. During the reaction, one cation cannot react with multiple ions at the same time, such as Ni 2+ 、Ni 3+ 、Co 3+ , Mn 4+ The valence state is consistent, which will lead to the precipitation of the local doping elements in the matrix material. The precipitated substances will destroy the integrity of the coating layer.
[0076] In step S2, the mass ratio of X / LiNi a Co b Mn c M1 d M2 f O2 is 400ppm-4000ppm and added to the matrix material LiNiaCobMncM1 d M2 f O2 and nano-XB. Nano-XB is coated onto the matrix material LiNi in a mechanical fusion machine. a Co b Mn c M1 d M2 f The mixed materials are then placed in a sagger, for example, with a loading of 2kg-5kg / sagger. The mixed matrix material LiNi a Co b Mn c M1 d M2 f O2 and nano-XB can react, so that nano-XB is coated on the matrix material LiNi a Co b Mnc M1 d M2 f The surface of O2, nano-XB and the matrix material LiNi a Co b Mn c M1 d M2 f The free lithium on the surface of O2 reacts to generate Li g XBO h , and finally generate the positive electrode material. The positive electrode material needs to be screened to ensure that the particle size of the positive electrode material is uniform and to avoid stress concentration caused by the positive electrode material being too large or too small. For example, a vibrating screen is used for screening, wherein the mesh number of the vibrating screen is 200-400 mesh. After screening, the material is demagnetized with a permanent magnet bar to obtain the positive electrode material. Preferably, at room temperature, nano-XB and the matrix material LiNi a Co b Mn c M1 d M2 f The free lithium on the surface of O2 reacts to generate Li g XBO h This makes the preparation process of the positive electrode material simpler. Of course, in order to remove the moisture in the preparation process of the positive electrode material, heating can also be used to react and generate Li g XBO h .
[0077] Of course, heating can also be used to make nano-XB and the matrix material LiNi a Co b Mn c M1 d M2 f The free lithium on the surface of O2 reacts to form a coating layer. For example, the heating temperature is 120°C-200°C, as described above.
[0078] Since M1 and M2 of the present application are uniformly doped in the base material, M1 and M2 will not be locally gathered on the surface of the base material, so that the entire surface of the base material is covered with a coating layer.
[0079] In one example, the LiNi a Co b Mn c M1 d M2 f The surface of O2 has free lithium, and the concentration of the free lithium is 300ppm-1300ppm.
[0080] The free lithium on the surface of the matrix material can react with nano-XB to form a coating layer, which can increase the diffusion path of lithium ions. However, if the concentration of free lithium is too high, surface pollutants with poor conductivity such as Li2CO3 and LiOH will be formed. These surface pollutants will hinder the transmission of ions and electrons and increase impedance. If the concentration of free lithium is too low, a complete coating layer cannot be formed, resulting in the coating layer being unable to protect the matrix material. Optionally, the concentration of free lithium is 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200, 1300ppm, etc. Within this range, the coating agent nano-XB can quickly react with free lithium to form Li g XBO h , and form a complete and uniform coating.
[0081] In one example, the free lithium includes at least one of LiOH or Li2CO3.
[0082] LiOH can react with the coating agent nano-XB at room temperature to form a uniform coating layer on the surface of the substrate material. Li2CO3 can react with the coating agent nano-XB under heating, for example, the heating temperature is greater than or equal to 400°C.
[0083] Of course, free lithium can also be lithium sulfate, lithium chloride, lithium acetate, lithium oxalate, lithium nitrate, etc.
[0084] In one example, in LiNi a Co b Mn c M1 d M2 f In O2, the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is 0.8 to 1.6.
[0085] If the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is too high, the battery will generate severe heat during the charge and discharge process, and part of the Li cannot be effectively embedded or removed during the first charge and discharge process, thereby reducing the first charge and discharge efficiency of the battery. If the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is too low, the energy density of the battery will be too low. Optionally, the above ratio is 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, etc.
[0086] Within this range, by precisely controlling the molar ratio of Li to transition metals (Ni, Co, Mn), the electrochemical performance of the positive electrode material can be optimized, and the discharge capacity and cycle stability can be improved. In addition, the charge and discharge efficiency of the battery can be improved, and the polarization during the charge and discharge process can be reduced, thereby improving the energy density and power density of the battery.
[0087] In one example, LiNi a Co b Mn c M1 d M2 f The particle size D50 of O2 is 2 μm to 4 μm.
[0088] In this example, the particle size D50 refers to the particle size corresponding to when the volume distribution percentage of the material reaches 50%. Optionally, the particle size D50 is 2μm, 3μm, 4μm, etc. Within this range, the matrix material has a larger specific surface area, thereby increasing the surface energy and providing a greater driving force for sintering. LiNi a Co b Mn c M1 d M2 f O2 powder particles are smaller and have a larger contact area, which helps the bonding between particles and can reduce the sintering temperature. a Co b Mn c M1 d M2 f O2 powder is easier to fill and pack tightly, reducing the porosity during sintering. In addition, the grain growth rate can be slowed down, which helps to obtain a finer grain size, thereby improving the mechanical properties of the material. During the charge and discharge process, the structural stability of the positive electrode material is crucial to the cycle life of the battery. The molar ratio of Li to transition metal within the above range can improve the structural stability of the positive electrode material, thereby improving the long-term performance of the battery.
[0089] In one example, LiNi a Co b Mn c M1 d M2 f The specific surface area of O2 is 0.6 to 1.4 m 2 / g.
[0090] LiNi a Co b Mn c M1 d M2 f If the specific surface area of O2 is too small, LiNi a Co b Mn cM1 d M2 f O2 has low reactivity and is not easy to react with nano-XB. a Co b Mn c M1 d M2 f If the specific surface area of O2 is too large, there will be too many active sites exposed on its surface, which may easily cause side reactions. a Co b Mn c M1 d M2 f The specific surface area of O2 is 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, etc. Within this range, the matrix material has a large specific surface area, which increases the surface energy and provides a greater driving force for sintering, making LiNi a Co b Mn c M1 d M2 f The sintering temperature of O2 is low and the occurrence of side reactions is avoided.
[0091] In one example, during the sintering, the mixed materials are first sintered at 500° C. to 800° C. for 1 to 3 hours, and then the temperature is raised to 850° C. to 1100° C. and sintered for 8 to 20 hours.
[0092] As mentioned above, in this example, sintering is first performed at a lower temperature and then at a higher temperature. At a lower initial sintering temperature, the growth rate of the grains can be slowed down to avoid excessive grain size, thereby maintaining the cyclic stability and structural integrity of the material, and helping to densify the material and reduce porosity. Sintering at a lower temperature can reduce stress inside the material and help improve the structural stability of the material. In addition, by sintering at different temperatures, the microstructure of the positive electrode material, such as grain size, morphology, and orientation, can be optimized, thereby improving the electrochemical performance of the battery.
[0093] In one example, the LiNi a Co b Mn c M1 d M2f O2 and the coating agent are mixed and reacted to generate the positive electrode material, the coating agent forms the coating layer, and the coating agent includes nano-XB. The steps include: reacting the mixed material at 120°C-200°C for 2 hours to 12 hours.
[0094] Optionally, the reaction temperature is 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc. The reaction time is 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In this example, the coating agent nano-XB reacts with free lithium to generate Li g XBO h Water will be generated during the process. Within this temperature range, on the one hand, it can accelerate the reaction rate between the coating agent nano-XB and free lithium; on the other hand, it can remove the water in the product, thereby reducing the adverse effects of water on the charge and discharge performance of the positive electrode material.
[0095] In one example, the precursor Ni a Co b Mn c The particle size D10, particle size D5 and particle size D90 of (OH)2 satisfy: D50 is 2μm-4μm; (D90-D10) / D50=0.5-0.7.
[0096] In this example, particle size D10, particle size D50 and particle size D90 are the particle sizes corresponding to the volume distribution percentages of 10%, 50% and 90% respectively. If the ratio (D90-D10) / D50 is too large, the particle size distribution will be wide, with more large particles and a small amount of small particles. a Co b Mn c M1 d M2 f The electrochemical performance of O2 is uneven, for example, there are differences in charge and discharge rates and inconsistent capacity decay. If the (D90-D10) / D50 ratio is too small, the particle size distribution is narrow, that is, the particle sizes are relatively close. Although this is beneficial to LiNi a Co b Mn c M1 d M2 f The electrochemical stability of O2 causes LiNi a Co b Mn c M1 d M2 fO2 has a lower rate performance and capacity. Optionally, D50 is 2 μm, 3 μm, 4 μm, etc. (D90-D10) / D50 is 0.5, 0.6, 0.7, etc. In this example, the above range indicates that the precursor Ni a The particle size distribution of CobMnc(OH)2 is relatively concentrated. This allows the positive electrode material to achieve more uniform shrinkage and densification during the sintering process, reducing the formation of pores and cracks. The concentrated particle size distribution makes the structure of particle size D10, particle size D5 and particle size D90 highly stable, reducing the rupture of the positive electrode material due to stress concentration during the charge and discharge process. By optimizing the particle size distribution as mentioned above, the LiNi a Co b Mn c M1 d M2 f Energy density of O2.
[0097] In one example, the Li in the lithium source and the precursor Ni a Co b Mn c The molar ratio of (OH)2 is 0.8 to 1.6.
[0098] Li in lithium source and Ni precursor a Co b Mn c If the molar ratio of (OH)2 is too large, the lithium content in the matrix material will be too high. Excessive lithium content may cause excessive volume changes in the matrix material during the charge and discharge process, resulting in instability of the material structure, thus affecting the cycle life and safety of the battery. a Co b Mn c The molar ratio of (OH)2 is too small, resulting in insufficient lithium content in the matrix material and low energy density. Optionally, the molar ratio is 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, etc. Within the above range, by precisely controlling the molar ratio of Li to the precursor in the lithium source, the crystal structure of the positive electrode material can be maintained, the structural distortion during the charge and discharge process can be reduced, and the cycle life of the battery can be improved; a matrix material with an ideal stoichiometric ratio can be formed, thereby improving the discharge capacity and cycle stability of the battery. By adjusting the molar ratio of Li to the precursor in the lithium source, the thermal stability of the positive electrode material can be improved, and the phase change and structural degradation that may occur at high temperatures can be reduced.
[0099] In one example, the particle size D50 of the nano-XB is 1 μm to 5 μm; the specific surface area of the nano-XB is greater than 5 m 2 / g.
[0100] In this example, the smaller particle size D50 of the nano-XB makes the coating layer have a larger specific surface area, which is conducive to the rapid transmission of lithium ions and improves the charge and discharge performance of the battery. However, too small a particle size D50 will result in too small gaps between particles, increase the difficulty of electrolyte penetration, and be unfavorable for the transmission of lithium ions. Optionally, the particle size D50 of the nano-XB is 1μm, 2μm, 3μm, 4μm, 5μm, etc. Within this range, the lithium ion transmission efficiency of the positive electrode material is high and the charge and discharge performance of the battery is excellent.
[0101] The larger specific surface area of nano-XB increases the contact area between the coating and the electrolyte, improving the ion transmission efficiency. However, too large a specific surface area will increase the side reactions between the electrolyte and the coating, affecting the stability and safety of the positive electrode material. 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, etc. Within this range, the cathode material has high ion transport efficiency and good stability and safety.
[0102] According to another embodiment of the present application, a battery is provided. The battery includes the positive electrode material described in the present application and has excellent charge and discharge performance.
[0103] The battery has good high and low temperature charging and discharging performance and safety performance.
[0104] According to another embodiment of the present application, an electric device is provided, which includes the battery described in the present application.
[0105] The electrical equipment has the characteristics of good charging and discharging performance and high safety factor.
[0106] Example 1
[0107] Precursor Ni a Co b Mn c (OH)2 is Ni 0.615 Co 0.20 Mn 0.185 (OH)2. M1M2Ox is Zr 0.9 Y 0.2 O 2.1 Among them, Zr and Ni 0.615 Co 0.20 Mn 0.185The molar ratio of (OH)2 is 0.002. The particle size D50 of the precursor is 3.625 μm, (D90-D10) / D50=0.591. The synthesis method of the precursor is an intermittent method. The specific surface area of the precursor is BET=17.92 m 2 / g, tap density TD = 1.45g / cm 3 The impurity content of the precursor is Na=69ppm, S=788ppm. The primary crystals of the precursor are needle-shaped. In the XRD test, FWHM(001)=0.36, FWHM(101)=0.7, and the MI of the magnetic material is 37ppb.
[0108] The lithium source includes: LiOH·H2O and Li2CO3. The molar ratio of the two is M(LiOH·H2O) / M(Li2CO3)=3:7. The ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn, that is, M(Li) / M(Ni+Co+Mn)=1.1.
[0109] nano-XB is nano-WB. Where W = 57.86wt%, B = 3.5wt%, particle size D50 = 1.15μm, specific surface area BET = 20m 2 / g.
[0110] In step S1, the above raw materials are added to a high-speed mixer in the above proportions, stirred at a medium speed of 650 rpm for 4 minutes, and then stirred at a high speed of 2000 rpm for 35 minutes. The mixed material is placed in a crucible with a loading capacity of 2 kg. The crucible is placed in a box furnace and sintered in an oxygen atmosphere, for example, the oxygen content is 99.5%. First, the temperature is raised to 500°C and kept warm for 1 hour, and then the temperature is raised to 850°C and kept warm for 8 hours. After sintering is completed, the sintered material is pulverized in an air flow mill. For example, the separation motor frequency of the air flow mill is 125 Hz, the feeding motor frequency is 5 Hz, the dust collection backflush / interval time is 10s / 0.5s, and the air pressure is 0.8 MPa. After pulverization, a matrix material with an average primary particle size of 1.95 μm is obtained, and the matrix material is a single crystal material. The chemical formula of the matrix material is LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Y 0.0004 O2, namely NCMZrY. Through electron microscope observation, the matrix material has no agglomeration.
[0111] In step S2, according to W / LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Y 0.0004The mass fraction of O2 is 3000ppm and added to the matrix material LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Y 0.0004 O2 and nano-WB. Nano-WB is coated onto the matrix material LiNi in a mechanical fusion machine. 0.615 Co 0.20 Mn 0.185 Zr 0.002 Y 0.0004 The surface of O2. Then, the mixed materials are placed in a sagger with a loading of 2kg / sagger. The sagger is placed in a box furnace and reacted at 135°C for 8 hours under an air atmosphere. After the reacted materials are cooled, they are passed through a vibrating screen, for example, the screen mesh number is 400 meshes. The sieved materials are demagnetized with a permanent magnet bar, that is, in the matrix material LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Y 0.0004 A coating layer is formed on the surface of O2, and the chemical formula of the coating layer is: Li 3.944 W 0.972 BO 7.888 Finally, the positive electrode material, namely NCMZrYWB, is obtained. The average primary particle size of NCMZrYWB is 1.95 μm. The coating layer is entirely covered on the surface of the base material. The coating layer is evenly distributed on the surface of the base material.
[0112] Example 2
[0113] The precursor NiaCobMnc(OH)2 is Ni 0.615 Co 0.20 Mn 0.185 (OH)2. M1M2Ox is Zr 0.8 Al 0.4 O 2.2 . Zr and Ni 0.615 Co 0.20 Mn 0.185 The molar ratio of (OH)2 is 0.002. The particle size D50 of the precursor is 3.625 μm, (D90-D10) / D50=0.591. The synthesis method of the precursor is an intermittent method. The specific surface area BET=17.92 m 2 / g, tap density TD = 1.45g / cm 3 The impurity content of the precursor is Na=69ppm, S=788ppm. The primary crystals of the precursor are needle-shaped. In the XRD test, FWHM(001)=0.36, FWHM(101)=0.7, and the MI of the magnetic material is 37ppb.
[0114] The lithium source includes: LiOH·H2O and Li2CO3. The molar ratio of the two is M(LiOH·H2O) / M(Li2CO3)=3:7. The ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn, that is, M(Li) / M(Ni+Co+Mn)=1.1.
[0115] In step S1, the above raw materials are added to a high-speed mixer in the above proportions, stirred at a medium speed of 650 rpm for 4 minutes, and then stirred at a high speed of 2000 rpm for 35 minutes. The mixed material is placed in a crucible with a loading capacity of 2 kg. The crucible is placed in a box furnace and sintered in an oxygen atmosphere, wherein the oxygen content is 99.5%. First, the temperature is raised to 500°C and kept warm for 1 hour, and then the temperature is raised to 850°C and kept warm for 8 hours. After sintering is completed, the sintered material is pulverized in an air flow mill. For example, the separation motor frequency of the air flow mill is 125 Hz, the feeding motor frequency is 5 Hz, the dust collection backflush interval / time is 10s / 0.5s, and the air pressure is 0.8 MPa. After pulverization, a matrix material with an average primary particle size of 1.56 μm is obtained, and the matrix material is a single crystal material. The chemical formula of the collective material is LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Al 0.001 O2, namely NCMZrAl. Through electron microscope observation, the matrix material has no agglomeration.
[0116] In step S2, according to W / LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Al 0.001 The mass fraction of O2 is 3000ppm. The S2 step method of Example 1 is used to prepare the matrix material LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.002 Al 0.001 The surface of O2 forms a coating layer, and the chemical formula of the coating layer is: Li 3.944 W 0.972 BO 7.888 Finally, the positive electrode material, namely NCMZrAlWB, is obtained. The average primary particle size of NCMZrYWB is 1.56 μm. The coating layer is entirely covered on the surface of the base material. The coating layer is evenly distributed on the surface of the base material.
[0117] Comparative Example 1
[0118] The precursor NiaCobMnc(OH)2 is Ni 0.615 Co 0.20Mn 0.185 (OH)2. The dopant is a mixture of nano ZrO2 and nano Y2O3. 0.615 Co 0.20 Mn 0.185 The molar ratio of (OH)2 is 0.002, Y and Ni 0.615 Co 0.20 Mn 0.185 The molar ratio of (OH)2 is 0.0004. The particle size D50 of the precursor is 3.625 μm, (D90-D10) / D50=0.591. The synthesis method of the precursor is an intermittent method. The specific surface area BET=17.92 m 2 / g, tap density TD = 1.45g / cm 3 The impurity content of the precursor is Na=69ppm, S=788ppm. The primary crystals of the precursor are needle-shaped. In the XRD test, FWHM(001)=0.36, FWHM(101)=0.7, and the MI of the magnetic material is 37ppb.
[0119] The lithium source includes: LiOH·H2O and Li2CO3. The molar ratio of the two is M(LiOH·H2O) / M(Li2CO3)=3:7, and the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is M(Li) / M(Ni+Co+Mn)=1.1.
[0120] The coating agent includes nano WO3 and boric acid.
[0121] In step one, the above raw materials are added to a high-speed mixer in the above proportions, stirred at a medium speed of 650 rpm for 4 minutes, and then stirred at a high speed of 2000 rpm for 35 minutes. The mixed material is placed in a crucible with a filling amount of 2 kg. The crucible is placed in a box furnace and sintered in an oxygen atmosphere, for example, the oxygen content is 99.5%. First, the temperature is raised to 500°C and kept warm for 1 hour, and then the temperature is raised to 850°C and kept warm for 8 hours. After sintering is completed, the sintered material is pulverized in an air flow mill. For example, the separation motor frequency of the air flow mill is 125 Hz, the feeding motor frequency is 5 Hz, the dust collection backflush / interval time is 10s / 0.5s, and the air pressure is 0.8 MPa. After pulverization, the matrix material LiNi with an average primary particle size of 1.91 μm is obtained. 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 O2, that is, NCMZr'Y'.
[0122] In step 2, according to W / LiNi 0.615 Co0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 The mass fraction of O2 is 3000ppm, B / LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 The mass fraction of O2 is 181ppm and added to the matrix material LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 O2 and nano WO3, H3BO3. In the mechanical fusion machine, the coating material H3BO3, WO3 is coated onto the base material LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 The surface of O2. Then, the mixed materials are placed in a sagger with a loading of 2kg / sagger. The sagger is placed in a box furnace and reacted at 135°C for 8 hours under an air atmosphere. After the reacted materials are cooled, they are passed through a vibrating screen, for example, the screen mesh number is 400 meshes. The sieved materials are demagnetized with a permanent magnet bar to obtain the final LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 O2@Li 3.944 W' 0.972 B'O 7.888 , namely NCMZr'Y'W'B'. The average primary particle size of NCMZr'Y'W'B' is 1.91 μm. In this example, since ZrO2 and Y2O3 are locally aggregated on the surface of the base material, and the reaction rate of nano-WO3 with free lithium is slow at low temperature, comparative example 1 forms an island-shaped coating layer on the surface of the base material instead of forming a whole coating layer.
[0123] Comparative Example 2
[0124] The lithium source includes: LiOH·H2O and Li2CO3, wherein M(LiOH·H2O) / M(Li2CO3)=3:7, and M(Li) / M(Ni+Co+Mn)=1.1.
[0125] The precursor NiaCobMnc(OH)2 is Ni 0.615 Co 0.20 Mn 0.185 (OH)2. The dopant is a mixture of nano ZrO2 and nano gas phase Al2O3. Zr and Ni 0.615Co 0.20 Mn 0.185 The molar ratio of (OH)2 is 0.002, Al and Ni 0.615 Co 0.20 Mn 0.185 The molar ratio of (OH)2 is 0.001.
[0126] In step 1, LiNi was synthesized according to the method of step 1 in comparative example 1. 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Al' 0.001 O2, namely NCMZr'Al', the average primary particle size of NCMZr'Al' is 1.55μm.
[0127] In step 2, according to W / LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 The mass fraction of O2 is 3000ppm, B / LiNi 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Y' 0.0004 The mass fraction of O2 is 181ppm, and LiNi is prepared by using nano WO3 and H3BO3, NCMZr'Al' according to the method of step 2 in comparative example 1. 0.615 Co 0.20 Mn 0.185 Zr' 0.002 Al' 0.001 O2@Li 3.944 W' 0.972 B'O 7.888, That is, NCMZr'Al'W'B'. The average primary particle size of NCMZr'Al'W'B' is 1.55 μm. In this example, since ZrO2 and Al2O3 are locally aggregated on the surface of the base material, and the reaction rate of nano WO3 with free lithium is slow at low temperature, comparative example 2 forms an island-shaped coating layer on the surface of the base material instead of forming an overall coating layer.
[0128] The following are performance tests of embodiments and comparative examples.
[0129] SEM Testing
[0130] The morphology of the positive electrode material prepared in Example 1 was analyzed by scanning electron microscopy, with a scanning voltage of 3KV and magnifications of 3K×, 5K×, 10K×, 30K×, and 50K×. The powder sample was adhered to a conductive tape, and the sample was dried and stored in a vacuum drying oven before testing.
[0131] Battery preparation and testing
[0132] The three materials were mixed in a mass ratio of positive electrode material: conductive agent: PVDF = 100:2.5:2.5, wherein PVDF was a 5% PVDF / NMP solution. After mixing, the slurry was passed through a 200-mesh screen. On a coating machine, the slurry was coated on one side of an aluminum foil to form an electrode sheet. Then, the electrode sheet was dried in an oven at 120°C. Next, a sampler was used to cut positive electrode discs with a diameter of d = 15 mm, and a metal lithium sheet was used for the negative electrode. Celgard 2300 microporous membrane was used as the diaphragm. The electrolyte included LiPF6 and a solvent. The solvent included ethylene carbonate and dimethyl carbonate, and the volume ratio of the two was 1:1. The concentration of LiPF6 in the electrolyte was 1 mol / L. CR2025 button cells were assembled in a glove box. The button cells were electrochemically tested using a battery testing system, and the relevant test conditions were as follows.
[0133] Specific capacity test:
[0134] Charge to 4.3V at 0.1C (1C = 180mA / g) constant current and constant voltage, with a cut-off current of 0.01C; then discharge to 2.5V at 0.1C constant current. Calculate the charge specific capacity, discharge specific capacity, and first efficiency.
[0135] Low temperature efficiency test:
[0136] At room temperature, the button cell was charged and discharged twice at 0.1C (1C = 180mA / g), then charged to 4.3V at 1C. The button cell was placed in a -20℃ constant temperature cabinet and discharged to 3V at 1C. The ratio of the low-temperature discharge specific capacity to the room-temperature 1C charge specific capacity was calculated.
[0137] Rate performance test:
[0138] Charge to 4.3V at 0.1C constant current and constant voltage, with a cut-off current of 0.01C; then, discharge to 2.5V at constant currents of 0.1C, 0.2C, 0.5C, and 1C, respectively, and calculate the 1C / 0.1C capacity retention rate.
[0139] Cycle test:
[0140] Under normal temperature conditions, the battery is charged and discharged 100 times, and the battery capacity retention rate is calculated.
[0141] Same as normal temperature cycle test, the difference is that the battery is tested in a 45℃ constant temperature box.
[0142] Table 1 - Performance test results of the present application examples and comparative examples
[0143]
[0144] Depend on Figure 1 to Figure 2 It can be seen that the positive electrode material of Example 1 of the present application is in a granular form. Figures 3 to 10 It can be seen that the elements O, Ni, Co, Mn, Zr, Y, W, and B in Example 1 of the present application are evenly distributed in the positive electrode material, and there is no element segregation phenomenon. Fig.11 The chemical formula of the base material of the positive electrode material is shown to be LiNi 0.615 Co 0.20 Mn 0.185 Zr 0.00 2Y 0.0004 O2, the chemical formula of the coating is Li 3.944 W 0.972 BO 7.888 .
[0145] By comparing the positive electrode material prepared in Example 1 of the present application (i.e., NCMZrYWB) with the positive electrode material prepared in Comparative Example 1 (i.e., NCMZr'Y'W'B'), it can be seen that NCMZrYWB has higher low-temperature efficiency, discharge specific capacity, first efficiency and cycle performance. This is mainly due to: ① The doping elements Zr and Y in NCMZr'Y'W'B' are locally aggregated and unevenly distributed in the matrix material; ② At low temperatures, the additive WO3 cannot generate Li2WO4, so NCMZr'Y'W'B' cannot form a coating that covers the entirety of the matrix material at low reaction temperatures; ③ The elements in the coating layer of NCMZrYWB are more evenly distributed than those in NCMZr'Y'W'B', thereby being able to generate Li2WO4 in situ with good conductive properties. 3.944 W 0.972 BO 7.888 Coating layer.
[0146] Comparing the positive electrode material prepared in Example 2 of the present application (i.e., NCMZrAlWB) with the positive electrode material prepared in Comparative Example 2 (i.e., NCMZr'Al'W'B'), it can be seen that NCMZrAlWB has higher low-temperature efficiency, discharge specific capacity, first efficiency and cycle performance. This is mainly due to: ① The doping elements Zr and Al in NCMZrAlWB are locally aggregated and unevenly distributed in the matrix material; ② At low temperatures, the additive WO3 cannot generate Li2WO4, so NCMZr'Al'W'B' cannot form a coating that covers the entirety of the matrix material at such a low temperature; ③ The elements in the coating layer of NCMZrAlWB are more evenly distributed than those in NCMZr'Al'W'B', thereby generating Li2WO4 in situ with good conductive properties. 3.944 W 0.972 BO 7.888 Coating layer.
[0147] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.
[0148] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a base material and a coating layer coated on the surface of the base material, wherein the coating layer covers the surface of the base material, and the chemical formula of the base material is LiNi a Co b Mn c M1 d M2 f O2, the chemical formula of the coating layer is Li g XBO h , wherein a is 0.6 to 0.95, b is 0.02 to 0.20, c is 0.03 to 0.20, d is 0.002 to 0.02, f is 0.0004 to 0.01, g is 2.025 to 4, h is 4.0875 to 8, M1 is Zr, M2 is at least one of Y and Al, X is one of Ti, Zr, Al, Mg, Zn, V, Ru, Y, W, Na, K, Rb, Cs, Sc, Nb, Bi, Co, Ni, Mn, Mo, Ta, Sr, La, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence state is the same.
2. The positive electrode material according to claim 1, characterized in that The molar ratio of B to X is from 0.5 to 1.
3. The positive electrode material according to claim 1, characterized in that X and the LiNi a Co b Mn c M1 d M2 f The mass ratio of O2 is 400ppm to 4000ppm.
4. The positive electrode material according to claim 1, characterized in that M1 and the LiNi a Co b Mn c M1 d M2 f The molar ratio of O2 is 0.002 to 0.
02.
5. The positive electrode material according to claim 1, characterized in that The molar ratio of M1 to M2 is 2 to 4.
5.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: include: The precursor Ni a Co b Mn c (OH)2, lithium source, M1M2Ox are mixed and sintered to obtain the matrix material, and the valence state of M1 is the same as that of Mn 4+ The valence state of M2 is the same as that of Co 3+ 、Ni 3+ The valence state is the same; The LiNi a Co b Mn c M1 d M2 f O2 and a coating agent are mixed and reacted to generate the positive electrode material, and the coating agent forms the coating layer, and the coating agent includes nano-XB.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The LiNi a Co b Mn c M1 d M2 f The surface of O2 has free lithium, and the concentration of the free lithium is 300ppm-1300ppm.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The free lithium includes at least one of LiOH or Li2CO3.
9. The method for preparing the positive electrode material according to claim 6, characterized in that: In the LiNi a Co b Mn c M1 d M2 f In O2, the ratio of the molar content of Li to the total molar content of the three elements Ni, Co and Mn is 0.8 to 1.
6.
10. The method for preparing the positive electrode material according to claim 6, characterized in that: The LiNi a Co b Mn c M1 d M2 f The specific surface area of O2 is 0.6 g / cm 3 Up to 1.4g / cm 3 .
11. The method for preparing the positive electrode material according to claim 6, characterized in that: In the sintering, the mixed materials are first sintered at 500° C. to 800° C. for 1 to 3 hours, and then the temperature is raised to 850° C. to 1100° C. and sintered for 8 to 20 hours.
12. The method for preparing the positive electrode material according to claim 6, characterized in that: The LiNi a Co b Mn c M1 d M2 f O2 and the coating agent are mixed and reacted to generate the positive electrode material, the coating agent forms the coating layer, and the coating agent includes nano-XB. The steps include: reacting the mixed material at 120°C-200°C for 2 hours to 12 hours.
13. The method for preparing the positive electrode material according to claim 6, characterized in that: In the M1M2O x , x = 2.1 to 2.
2.
14. The method for preparing the positive electrode material according to claim 6, characterized in that: The precursor Ni a Co b Mn c The particle size D10, particle size D50 and particle size D90 of (OH)2 satisfy: D50 is 2μm-4μm; (D90-D10) / D50=0.5-0.
7.
15. The method for preparing the positive electrode material according to claim 6, characterized in that: The lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium sulfate, lithium chloride, lithium acetate, lithium oxalate and lithium nitrate.
16. The method for preparing the positive electrode material according to claim 6, characterized in that: The Li in the lithium source and the precursor Ni a Co b Mn c The molar ratio of (OH)2 is 0.8 to 1.
6.
17. The method for preparing the positive electrode material according to claim 6, characterized in that: The particle size D50 of the nano-XB is 1 μm to 5 μm; the specific surface area of the nano-XB is greater than 5 m 2 / g.
18. A battery, characterized in that: The invention comprises a positive electrode material as claimed in any one of claims 1 to 5 or a positive electrode material prepared by the method for preparing the positive electrode material as claimed in any one of claims 6 to 17.
19. An electrical equipment, characterized in that: Comprising a battery as claimed in claim 18.